An unconventional autophagic pathway that inhibits ATP secretion during apoptotic cell death - Elena Terraza-Silvestre; Raquel Villamuera; Julia Bandera-Linero; Michal Letek; Daniel Oña-Sánchez; Cristina Ramón-Barros; Clara Moyano-Jimeno; Felipe X. Pimentel-Muiños (Nature Communications)
Abstract Mobilisation of Damage-Associated Molecular Patterns (DAMPs) determines the immunogenic properties of apoptosis, but the mechanisms that control DAMP exposure are still unclear. Here we describe an unconventional autophagic pathway that inhibits the release of ATP, a critical DAMP in immunogenic apoptosis, from dying cells. Mitochondrial BAK activated by BH3-only molecules interacts with prohibitins and stomatin-1 through its latch domain, indicating the existence of an interactome specifically assembled by unfolded BAK. This complex engages the WD40 domain of the autophagic effector ATG16L1 to induce unconventional autophagy, and the resulting LC3-positive vesicles contain ATP. Functional interference with the pathway increases ATP release during cell death, reduces ATP levels remaining in the apoptotic bodies, and improves phagocyte activation. These results reveal that an unconventional component of the autophagic burst that often accompanies apoptosis sequesters intracellular ATP to prevent its release, thus favouring the immunosilent nature of apoptotic cell death.